MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN AIRBRUSH PADA ANAK USIA 5-6 TAHUN DI TK ISLAM AKRAMUNNAS PEKANBARU - Nurul Riana; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of these research are: 1) To improve ability of fine motor in the children age 5-6 years old through airbrush activities at the Islamic Kindergarten Akramunnas Pekanbaru, 2) To know how to apply airbrush in order to improve ability of fine motor for the children aged 5-6 years old at the Islamic Kindergarten Akramunnas Pekanbaru. 3) To know the magnitude of the influence of airbrush activity on fine motor ability of the children age 5-6 years old at the Islamic Kindergarten Akramunnas Pekanbaru. This form of research is Collaborative Class Action Research. Research tool that used the data is the research instrument by using observation sheet which consist of 7 indicators of fine motor ability. Based on the result of the research the indicated in every meeting cycle any incresing can be seen through of the result percentage of fine motor ability of the child, with the percentage value before the 40,02% cycle, the first is 45,08% cycle and the second is 79.85%. It can be seen from the improvement the data of the children, before the treatment the first cycle that is 12,64%, and then the first cycle to the scond cycle that is 77,12% an then before treatment to the second cycle that is 99,52%. The result based on the research is the airbrush activity can incresing fine motor ability of the children age 5-6 years old at the Islamic Kindergarten Akramunnas Pekanbaru. The improvement of the researc according of the expectations of the researcher made it in this study.Keywords: Fine Motor, Airbrush Activities